Mendukung Keberlanjutan - H.K, Ajeng Pramesthy; Syahna, Adinda; Mulya, Kukuh Budi (INTERDISCIPLINARY JOURNAL ON LAW, SOCIAL SCIENCES AND HUMANITIES, 2024)
Indonesia is an archipelagic country with vast marine areas. The sea is one of its greatest assets due to its diverse marine ecosystems, including both flora and fauna, as well as valuable mineral resources. However, with the advancement of time, the sustainability of marine ecosystems is threatened by mining activities and exploitation. In particular, exploitative activities carried out by foreign nationals in Indonesian waters often disregard binding legal protections. Therefore, protecting Indonesia's marine areas in the international arena is an urgent matter for the Indonesian government. The United Nations Convention on the Law of the Sea (UNCLOS) of 1982, accompanied by Indonesian regulations, provide detailed regulations regarding the protection and preservation of Indonesia's marine ecosystems. Consequently, it is hoped that these efforts can address issues arising from pollution and damage in Indonesia's territorial waters and Exclusive Economic Zone. This article aims to understand the role of international legal protection in preserving Indonesia's marine ecosystems. Additionally, it assesses how the government responds to the limited role of Indonesian positive law in marine ecosystem preservation, from the perspective of international maritime law. This article utilizes normative legal writing, drawing references from relevant literature, library materials, and applicable legal regulations as concrete data sources. Keywords : UNCLOS 1982, Legal Protection, Marine Environment.